SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN WARNA KEMASAN MENGGUNAKAN METODE PROFILE MATCHING (BERDASARKAN REKOMENDASI WARNA KEMASAN YANG DISARANKAN OLEH ERIC P.DANGER) (Information Technology and Telematics, 2013)
The selection of colors in the design of the packaging of a product becomes important because the color has a big impact in the marketing of a product. A consultant of colors research Eric P. Danger provides recommendations on the use of packaging color. To facilitate the selection of colors as recommended by Eric P. Danger, we need a program that can make the process of color selection. The color selection system program serves to provide conformity assessment between the color profile and the product profile using profile matching method. The system operates by using the parameters inputted by the user to do the profile matching process. Results of a profile matching process are color values, color profile match detail, and color application advice on product packaging as a recommendation for the user to choose the color of the packaging of a product.Keywords : Color Selection System, Packaging, Profile Matching Method, Eric P. Danger.